Least developed countries and geographical indications: how can Uganda position itself to benefit from geographical indications? - Kisuule, Yvonne Alexandra (Intellectual Property Research Unit, 2015)
The primary objective of this thesis is to determine how Uganda can optimally benefit from geographical indications. This objective is achieved by focusing on the current negotiations at the World Trade Organization concerning geographical indications. The main issues in contention are the extension of a higher level of protection to other products, besides wines and spirits, and the establishment of a multilateral register for wines and spirits. In the discussion of these issues, each proposal is examined in light of Uganda's interests. The thesis also focuses on how geographical indications can be turned into development tools at the national level. It considers Uganda's legislation, the Geographical Indications Act 8 of 2013, and highlights the provisions that might deter the establishment of a successful geographical indications system in the country. The thesis then identifies other factors that Uganda must address in order for geographical indications to become development tools. It is concluded that in order to establish a successful geographical indications system, Uganda needs to continue its support for the Modalities Proposal in the international negotiations. Furthermore, at the national level, there are various factors that must be addressed, beyond the law, before geographical indications can become development tools, and these include the formation of producer organisations, marketing strategies and the sensitisation of stakeholders.